Current situation of endoscopic surgery for recurrent nasopharyngeal carcinoma - Hong-meng YU; Xi-cai SUN; Xiao-le SONG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Nasopharyngeal carcinoma (NPC) is one of the most common head and neck malignant tumors in China. Radiotherapy with or without concurrent chemotherapy is the first treatment option. The local recurrence rate of NPC after radiotherapy ranged from 10% to 40%. Re-irradiation could cause many serious complications for local recurrent or residual NPC after radiotherapy. Therefore, traditional open approach surgery and endoscopic surgery are becoming important alternative treatment options for locally recurrent NPC, especially the latter has such advantages as operating under direct vision, clear field of view, minimal invasion, short hospitalization and not affecting facial appearance.